2020
DOI: 10.29333/iji.2020.13226a
|View full text |Cite
|
Sign up to set email alerts
|

Receptiveness of Spanish and Flamenco Professional Dancers in Their Training and Development

Abstract: The concept of coaching is an important object of study in the development of sports coaches, and the relationship between athletes and coaches may define the professional life of the former. In the area of dance, the figure of the coach is represented by teachers, choreographers and directors; however, there are few studies that analyse the different forms of coaching and receptiveness in the training of dance professionals. Therefore, the aim of this study was to ascertain the receptiveness of professional S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Previous research on students of young age (elementary school) has also shown that dancing lessons is the most effective means to achieve social skills learning (Masadis et al, 2019). Younger dancers were also found to present a higher mean in receptiveness to coaching in the study conducted by de las Heras-Fernández, Coll, & Espada (2020).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Previous research on students of young age (elementary school) has also shown that dancing lessons is the most effective means to achieve social skills learning (Masadis et al, 2019). Younger dancers were also found to present a higher mean in receptiveness to coaching in the study conducted by de las Heras-Fernández, Coll, & Espada (2020).…”
mentioning
confidence: 71%
“…Be it professional or for leisure, dancing of all kinds attracts a large scale of participants. Dancers show different levels of receptiveness to coaching (de las Heras-Fernández et al, 2020). Greek dance courses and seminars are organized in various parts of Greece and abroad attracting both Greek and foreign participants.…”
mentioning
confidence: 99%